Walter A. Fairservis (Jr.) (Archaeological Surveys in the Zhob and Loralai Districts, West Pakistan) - Dani, Ahmad Hasan (Ancient Pakistan, 1965)
Walter A. Fairservis (Jr.) - Archaeological Surveys in the Zhob and Loralai Districts, West Pakistan, Anthropological Papers of the American Museum of Natural History, New York, 1959, Volume 47, Pt. 2. pp. 273-448, 25 Plates, 84 text figures.